Examining the Role of Safety Planning and Firearms in Community Professional’s Advice and Perceived Helpfulness for Female IPV Victims - Lynch, Kellie R. (Journal of family violence, 2021)
When IPV victims contact justice system or victim service professionals they are often advised on safety actions. Yet, there is limited research on what advice victims receive and how that advice might differ depending on where one lives (e.g., a rural versus urban area) or who is giving the advice (e.g., law enforcement versus victim advocates). The current study surveyed 133 justice system and victim service professionals who work with IPV victims in rural and urban communities. Three primary research questions were analyzed: (1) what advice do professionals give IPV victims with protective orders that had been violated?; (2) how helpful do professionals perceive six different safety strategies for IPV victims?; and (3) what role do firearms play in safety advice and perceived helpfulness among professionals? Contacting the criminal justice system was overwhelmingly the most common safety advice reported by all professionals. In comparison, less than one third of professionals mentioned safety planning and less than 20% mentioned seeking help from victim services despite these two responses being rated as the most helpful in the close-ended questions. Although obtaining a firearm was advised by few professionals and was perceived as unhelpful by most professionals, rural and justice system professionals were more likely than their counterparts to mention firearms in their advice and rate firearm-related protective behaviors as helpful. The results highlight the need to focus on improving first responder advice to victims and maximize training on the importance of safety planning in high-risk IPV circumstances.